2001
DOI: 10.1034/j.1600-0714.2001.300906.x
|View full text |Cite
|
Sign up to set email alerts
|

Levamisole and/or Chinese medicinal herbs can modulate the serum level of squamous cell carcinoma associated antigen in patients with erosive oral lichen planus

Abstract: The serum levels of squamous cell carcinoma associated antigen (SCCA) were determined by a microparticle enzyme immunoassay in a group of patients with stage I oral squamous cell carcinoma (OSCC), major or minor type erosive oral lichen planus (EOLP), recurrent aphthous stomatitis (RAS), Behçet's disease (BD), oral leukoplakia (OL), or oral submucous fibrosis (OSF), and in normal control subjects. About 97% of the normal control subjects and the patients with minor type EOLP, RAS, BD, OL or OSF had a serum lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 21 publications
0
23
1
Order By: Relevance
“…c Major type: patients with EOLP with oral erosion or ulceration >10 mm in diameter. [5][6][7] For example, all the patients with EOLP in our study showed either complete healing of EOLP lesions or the transformation of the EOLP to NEOLP after levamisole therapy. Multiple comparisons between patients and normal controls with *P < 0.05, **P < 0.01, ***P < 0.005, and ****P < 0.001.…”
Section: Reportmentioning
confidence: 57%
See 2 more Smart Citations
“…c Major type: patients with EOLP with oral erosion or ulceration >10 mm in diameter. [5][6][7] For example, all the patients with EOLP in our study showed either complete healing of EOLP lesions or the transformation of the EOLP to NEOLP after levamisole therapy. Multiple comparisons between patients and normal controls with *P < 0.05, **P < 0.01, ***P < 0.005, and ****P < 0.001.…”
Section: Reportmentioning
confidence: 57%
“…[5][6][7] Our previous studies found that treatment with levamisole for a period of 0.5-30 months significantly reduced the abnormally high serum level of squamous cell carcinoma-associated antigen (SCCA), interleukin (IL)-6 or IL-8 to normal levels. [5][6][7] Our previous studies found that treatment with levamisole for a period of 0.5-30 months significantly reduced the abnormally high serum level of squamous cell carcinoma-associated antigen (SCCA), interleukin (IL)-6 or IL-8 to normal levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also an area that requires further study. 47,51,52 In addition, further research is needed to discover the functional mechanisms of the above-described traditional medicines, and compare them with the other useful herbal medicines for OLP therapy. 45,47 Conclusions Treatment of OLP with prednisolone plus traditional medicinal herbs can improve symptoms, relieve pain, reduce recurrent severity, and prolong the disease-free period, is more costeffective, and has fewer side-effects of oral candidiasis than treatment with other medications.…”
Section: Groupmentioning
confidence: 98%
“…[16] Adverse affects of levamisole are mild and infrequent and include rash, nausea, abdominal cramps, taste alteration, alopecia, arthralgia and a flu-like syndrome and rarely cause agranulocytosis. [14] Agranulocytosis is commonly seen in those patients with human leukocyte antigen-B27 positivity and in those patients who have undergone long-term levamisole therapy.…”
Section: Levamisolementioning
confidence: 99%